SPATIAL ANALYSIS OF SUSTAINABLE MANGROVE TOURISM IN THE SERAMBI DELI COASTAL AREA, PANTAI LABU DISTRICT, NORTH SUMATRA - Daulay, Aulia Putra; Sari, Ratna (Jurnal Silva Samalas, 2026)
Mangrove ecotourism is largely unknown to the general public due to limited development and insufficient assessment of its suitability, especially in North Sumatra. Spatial analysis in determining the suitability of coastal areas is rarely conducted. This spatial analysis uses Geographic Information System (GIS) applications in determining the management model for mangrove forest areas. The purpose of this study is to determine how to manage and develop mangrove ecotourism through spatial analysis based on ecotourism-related parameters. This study was conducted from September to December 2025. The research methodology included an analysis of the suitability matrix of mangrove forests for ecotourism, a SWOT analysis to identify the strengths, weaknesses, and challenges in the suitability of land for ecotourism, and remote sensing analysis using ArcGIS 10.8 with Band 8 and Band 4 for NDVI. The results obtained were an Ecotourism Suitability Index value of 71.05%, which is classified as conditionally suitable, a SWOT analysis in the form of ecotourism development for promotion through social media and support for accessibility and ecotourism infrastructure, and remote sensing analysis with an average NDVI value of 0.36, which is classified as high density. The conclusion of this study is that the mangrove forest at Serambi Deli Beach is suitable for ecotourism development, but several conditions must be improved, including mangrove species diversity, mangrove density, and infrastructure to support ecotourism activities.